A parallel computing method for automatic license-plate detection on Windows-based computer cluster - Qian, Xiaodong (2008)
Computationally intensive tasks in computer vision and image processing are ideally implemented in parallel on a variety of parallel architectures, such as vector supercomputers and massively parallel processing (MPP) systems. As a cost effective alternative to these special architectures, a cluster of Personal Computers (PCs) are used in this thesis to implement the parallel applications. Four reasons are given as follows: (1) friendly user interface, (2) low cost, (3) the availability of reliable network operating system like Windows NT, and (4) high computing ability. The aim of this thesis is to build an effective parallel computing model on a cluster of PCs and investigate its practical utilization.